Model Literasi Keuangan untuk Penanggulangan Pembelian Kompulsif Berbasis Maqasid Syariah dalam Menguatkan Keluarga Sakinah: Financial Literacy Model for Addressing Compulsive Buying Based on Maqasid al-Shariah in Strengthening Sakinah Families - Muhammad Zuhdi; Muhammad Suaib Tahir (Direktorat Jenderal Bimbingan Masyarakat Islam, 2026)
Abstract Compulsive buying disorder has become a serious threat to the economic and psychological resilience of Muslim families in Indonesia. Data from the Financial Services Authority (2024) records a significant 23.4% year-on-year increase in household consumer debt, with 38% related to impulsive shopping behavior triggered by e-commerce and fintech platforms. This study aims to formulate a financial literacy model based on Maqasid Shariah with the hierarchy of dharuriyyat, hajiyyat, and tahsiniyyat to overcome this behavior. Using qualitative library research with an interdisciplinary approach, this study analyzes normative Islamic texts, contemporary consumer psychology literature, behavioral economics, and Ministry of Religious Affairs policy documents to build a holistic intervention framework. The results show that overcoming compulsive buying requires a tiered approach: (1) The dharuriyyat level in the form of emergency interventions to save the five basic principles (al-kulliyat al-khams); (2) The hajiyyat level in the form of cognitive barrier mechanisms and substitution activities to prevent relapse; and (3) The tahsiniyyat level in the form of building qana'ah character, wealth spirituality, and transformative financial literacy. This article concludes that this model has strategic implications for the Directorate General of Islamic Community Guidance, particularly in developing Marriage Guidance (Bimwin) modules, Islamic Family Counseling programs, mosque-based sharia financial literacy movements, and the